Virulence, phylogenetic background and antimicrobial resistance in Escherichia coli associated with extraintestinal infections - Katarína Čurová; Radka Slebodníková; Marta Kmeťová; Vladimír Hrabovský; Matúš Maruniak; Erika Liptáková; Leonard Siegfried (Elsevier, 2020)
Background: Escherichia coli (E. coli) is a major cause of urinary tract infections and bloodstream infections and an important agent in the resistance to antibiotics. The present study sought to determine associations between virulence, phylogenetic background and antimicrobial resistance of E. coli strains isolated from patients with extraintestinal infections. Methods: A total of three hundred ten E. coli strains were isolated from blood, skin and soft tissue and urine. PCR methods were used to detect four main phylogenetic groups (A, B1, B2 and D) and 11 virulence genes (3 toxins, 3 adhesins, 1 siderophore, 4 capsule synthesis proteins and protectins). Standard broth microdilution test was used to determine sensitivity to 12 antimicrobial drugs. Results: The most common and the most virulent phylogenetic group B2 was found in 193 (62.3%) isolates. The lowest virulence was observed among the group A. Analysis of virulence factors revealed the kpsMTII gene in 212 (68.4%), aer in 194 (62.6%) and tra in 184 (59.4%) of isolates, respectively. Multi-drug resistant (MDR) phenotype was noticed in 165 (53.2%) isolates. Lower representation of the MDR phenotype was detected in E. coli containing all groups of virulence genes and in the avirulent E. coli. Conclusions: Our study documented that E. coli associated with 3 different extraintestinal infections contain various virulence factors. Genes afa, pap, aer, neuC show significant differences among the 3 groups of the strains tested and might be the prerequisite virulence factors in bloodstream infections. Isolates containing all groups of virulence genes predominantly originate in the blood and belong to the B2 phylogenetic group. Overall, we identified significantly higher incidence of all the groups of virulence genes examined among the B2 group. Prevalence of the MDR phenotype and high levels of resistance to ampicillin, ciprofloxacin and trimetoprim/sulfamethoxazole reflect the trend observed worldwide in recent years.